The Effect of teacher motivation and instructional methodologies on student outcomes in integrated science in the upper east region, Ghana - Ibrahim, Issah; K. Eminah, John; Owusu-Fordjour, Collins; Afram Oware, Stephen; Baalongbuoro, Valantine (International Journal for Innovation Education and Research, 2023)
This study’s focus was to ascertain how teaching strategies and teacher motivation affected students’ performance in integrated science in Ghana’s Upper East. The researcher employed a survey design. Heads of senior high schools and teachers of integrated science constitute the study’s population. Purposeful and straightforward random samplings were utilised to choose the respondents. 84 respondents made up the sample, comprising 80 integrated science teachers and 4 school heads. A structured questionnaire served as the primary tool, and the Statistical Package for Social Sciences was used to analyse the data (SPSS). The data analysis revealed that a large percentage of integrated science instructors (52.5%) thought that teacher motivation led them to perform in-depth study in order to teach effectively. Additionally, it was found that every integrated science instructor stated that skilled teachers employ effective teaching strategies to raise student achievement.